The Effect Of Thin Capitalization, Capital Intensity, Profitability, Sales Growth And Company Age On Tax Avoidance With Firm Size As A Moderating Variable - Samino Hendrianto; Andre Ahmad Saputra; Nursimah Dara; Masturo Masturo (Universitas Muhammadiyah Tangerang, 2026)
The purpose of this study was to determine the effect of Thin Capitalization, Capital Intensity, Profitability, Sales Growth and Company Age on Tax Avoidance with Firm Size as a moderating variable in the energy sector listed on the Indonesia Stock Exchange (IDX). The research time period is 5 years, namely the 2018-2022 period. The population of this study includes all Energy sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2022. The sampling technique used purposive sampling technique. Based on the predetermined criteria, 18 companies were obtained. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analysis method used is panel data regression analysis. Partial research results show that Thin Capitalization has a positive effect on Tax Avoidance, Capital Intensity and Profitability have a negative effect on tax avoidance. Sales Growth and Company Age have no effect on tax avoidance. Firm size can moderate the effect of Thin Capitalization, Capital Intensity, Profitability on tax avoidance. Firm size cannot moderate the effect of Sales Growth and Company Age on tax avoidance